The Applications of Gold Nanoparticles in the Diagnosis and Treatment of Gastrointestinal Cancer - Yang, Zhijing; Wang, Dongxu; Zhang, Chenyu; Liu, Huimin; Hao, Ming; Kan, Shaoning; Liu, Dianfeng; Liu, Weiwei (Frontiers in Oncology, 2022)
.In recent years, the morbidity and mortality of gastrointestinal cancer have remained high in China. Due to the deep location of the gastrointestinal organs, such as gastric cancer, the early symptoms of cancer are not obvious. It is generally discovered at an advanced stage with distant metastasis and lymph node infiltration, making it difficult to cure. Therefore, there is a significant need for novel technologies that can effectively diagnose and treat gastrointestinal cancer, ultimately reducing its mortality. Gold nanoparticles (GNPs), a type of nanocarrier with unique optical properties and remarkable biocompatibility, have the potential to influence the fate of cancer by delivering drugs, nucleic acids to cancer cells and tissues. As a safe and reliable visualization agent, GNPs can track drugs and accurately indicate the location and boundaries of cancer, opening up new possibilities for cancer treatment. In addition, GNPs have been used in photodynamic therapy to deliver photosensitizers, as well as in combination with photothermal therapy. Therefore, GNPs can be used as a safe and effective nanomaterial in the treatment and diagnosis of gastrointestinal cancer.